Efektivitas Penggunaan Metode Bermain Berdansa Berirama Terhadap Pembelajaran Keterampilan Bola Voli - Persada, Yudha Bela; Setyawan, Danang Aji; Siswanto, Heri (Media Penelitian Pendidikan : Jurnal Penelitian dalam Bidang Pendidikan dan Pengajaran, 2025)
The purpose of this study is the effectiveness of the use of rhythmic dancing methods on the learning of passing skills over volleyball. This study is a quantitative research that uses an experimental approach with the method of playing rhythmic dance. The sampling technique applied is purposive sampling. This study uses a test as an instrument, the test used is a passing measurement test on a volleyball (Brumbach Forearm Pass Wall Volley Test). The normality test, homogeneity test, and hypothesis test are the analyses used in this study. The results of the study were on the passing skills of volleyball before learning to play by dancing rhythmically, the lowest score was 45, the highest score was 90, and the average was 63. In the upper passing skills after learning to play by dancing, the lowest score was 55, the highest score was 95, the average was 73.47. In addition to the statistical description of the data, this study also categorized the level of passing learning outcomes for volleyball after and before the treatment of learning to play by dancing rhythmically. Based on the results of the study, the conclusion in this study is that the application of learning to use learning to play by dancing rhythmically against the upper passing in volleyball in grade X students of SMA 11 Semarang increased by an average of 15.25%. This is also proven based on the comparison of the significance value obtained a score of 0.000 less than the reference of the significance norm of 0.05. For teachers, the model of learning to play in learning must often vary and be used often considering that students are more enthusiastic about learning by playing at school.